Malaysia and the Rome Statute : Domestic Debate Over? - Waikar, Prashant (2019)
In a span of a month, Malaysia first ratified the Rome Statute and then withdrew from the International Criminal Court that the treaty governs. This episode reveals how the Malaysian royalty and the opposition were able to pressure the Pakatan Harapan government, as well as the challenges the government continues to face one year into its tenure.